Determining Performance Evaluation Criteria For Employees and Leaders Using NVivo - Luthfi Daffa Hadi Pratama; Renny Rochani (KAMPUS AKADEMIK PUBLISING, 2026)
Purpose – This study aims to identify and determine performance evaluation criteria for employees and leaders in a company using NVivo. Design/methodology/approach – This research adopts a qualitative approach with supportive descriptive analysis. Data were collected through in-depth interviews with selected employees and leaders using purposive sampling. The interview data were analyzed using NVivo through coding techniques to identify key criteria and develop underlying dimensions (sub-criteria). Additionally, word frequency analysis was conducted to identify dominant terms frequently expressed by respondents, and the results were visualized using project maps to illustrate relationships between concepts. Findings – The results show that NVivo effectively identifies and structures performance evaluation criteria and their sub-criteria. For employees, the main criteria include attendance, attitude, discipline, and responsibility, each supported by several sub-criteria derived from interview data. For leaders, the criteria include leadership, decision-making, fairness, and responsibility, along with their respective sub-dimensions. Word frequency analysis highlights dominant themes discussed during interviews, strengthening the validity of the identified criteria. Practical implications – The use of NVivo provides companies with a systematic and data-driven approach to identifying performance evaluation criteria, enabling more structured and transparent assessment frameworks. Originality/value – This study contributes to performance management literature by focusing on the identification of both employee and leadership performance criteria simultaneously using NVivo, particularly by incorporating sub-criteria development and qualitative data visualization within the company context.